COMPARISONS BETWEEN INTAKE VALUES OBSERVED AND PREDICTED BY NUTRITIONAL SYSTEMS FOR CONFINED NELLORE CATTLE - Ferreira, Aline Maria Soares; da Silva, Simone Pedro; de Faria, Carina Carina Ubirajara; Mendes, Egleu Diomedes Marinho; Felipe, Ester Ferreira [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2021)
This study compared the dry matter intake (DMI) of Nellore heifers and bulls in the feedlot, predicted by the BR-Corte (2010 and 2016) and NRC (2000) nutritional systems. Hence, two experiments were conducted in a completely randomized design. The first one used 47 Nellore bulls, not castrated, with an average initial weight of 413 kg, and 19 months of age. The second experiment used 24 Nellore heifers with an average initial weight of 300 kg and 23 months of age. The accuracy and approximation of the DMI estimates by the nutritional systems were adjusted with the simple linear regression model and the root mean square error of prediction (RMSEP). The DMI was 8.06 kg day-1 for Nellore heifers and 11.54 kg day-1 for bulls, which are higher than the values predicted by the nutritional systems. The NRC (2000) and BR-Corte (2010 and 2016) underestimated DMI in 20.84, 20.09, and 19.35% for heifers and 28.07, 16.20, and 11.78% for bulls, respectively. It was concluded that the BR-Corte 2010 and 2016 were the most suitable models to estimate the DMI of Nellore heifers and bulls for higher precision and accuracy.
Keywords: Electronic Feeding Systems; Equations; Measurement; Nutrition